METODE PENGAKUAN KEUNTUNGAN PEMBIAYAAN MURABAHAH DI LEMBAGA KEUANGAN SYARIAH (Analisis Fatwa No: 84/DSN-MUI/XII/2012) - Asep Mulyani (TAHKIM, 2021)
Murabahah financing is a transaction for the sale of goods by stating the acquisition price and profit (margin) agreed by the seller and buyer. As for the implementation, murabaha financing uses the profit recognition method which refers to Fatwa No.84 / DSN-MUI / XII / 2012 and PSAK No. 102 about Murabaha. Based on the author's search results, there are two methods applied by Islamic Banking and Islamic Financial Institutions namely, the Proportional method and the Annuity method. The workings of these two methods can be seen from the process which includes, the Proportional method tends to refer to PSAK No. 10. While the Annuity method tends to refer to the DSN-MUI fatwa. Keywords: Murabahah, Method and Fatwa.